Study of the Elements Design Interactive of Student in Solar System Physics lessons through the Interactive Compact Disk (CD) of Solar System Physics Lab - Cahyadi, A T (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Multimedia can combine elements of text, sound, images, animation, and video via a computer or digitally manipulated elements that are conveyed or controlled interactively. Interactive multimedia in this learning can be a learning solution in the digital era to stimulate the thinking power of students. The purpose of this study was to determine the interactive multimedia element theory test used in the Interactive CD of Solar System Physics Lab as an electronic learning medium. This research method was carried out using a descriptive qualitative approach regarding the results of the study of the interactive multimedia design structure on the Interactive CD of Solar System Physics Lab, with case studies of researchers investigating carefully a program, event, activity, process, or group of individuals. Data processing techniques through literature study, group discussions, and interviews. The results of this study will determine the elements of interactive multimedia on the interactive CD of Solar System Physics Lab, which can be used as an example for e-learning media, the Solar System Physics Lab has used the Multimedia development process flow according to the procedure.